2020
DOI: 10.1080/13102818.2020.1803766
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and evaluation of Bacillus velezensis ZW-10 as a potential biological control agent against Magnaporthe oryzae

Abstract: Rice blast is one of the most destructive diseases of rice and is caused by the infection with rice blast fungus, Magnaporthe oryzae. In the present study, we obtained 12 bacterial isolates from Sichuan basin neutral purplish soil. Among them, the strain named ZW-10 showed significant activity against M. oryzae. Morphological and biochemical studies, along with 16S rDNA sequencing analysis, proved that the strain belongs to Bacillus velezensis. The cell-free culture filtrate of ZW-10 inhibited the growth of M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…It was found that the mycelia treated with 1% CFB showed obvious red fluorescence, especially the deformed mycelia and vacuolar area. In the previous experiment, we found that ZW10 could produce protease, cellulase and chitinase [22]. Therefore, the loss of mycelial permeability caused by 1% CFB treatment of M. oryzae may be related to this.…”
Section: Plos Onementioning
confidence: 83%
See 1 more Smart Citation
“…It was found that the mycelia treated with 1% CFB showed obvious red fluorescence, especially the deformed mycelia and vacuolar area. In the previous experiment, we found that ZW10 could produce protease, cellulase and chitinase [22]. Therefore, the loss of mycelial permeability caused by 1% CFB treatment of M. oryzae may be related to this.…”
Section: Plos Onementioning
confidence: 83%
“…Up to now, there are only a few reports on the control of rice blast by B. velezensis. Previous studies characterized the physical and chemical properties of B. velezensis ZW10 and elucidated its antagonistic activity against M. oryzae [22]. In this paper, we aimed to explore the inhibitory mechanism of B. velezensis ZW10 and the host defense response against M. oryzae, and to evaluate the potential of ZW10 as a biological pesticide.…”
Section: Introductionmentioning
confidence: 99%
“…Several strains of B. velezensis have also been reported to act as biocontrol agents, preventing plant diseases and promoting plant growth. For instance, B. velezensis strain ZW-10 exhibited activity against the Magnaporthe oryzae , via secondary metabolites ( Chen et al, 2020 ). It has been reported that B. velezensis strain 83 from the mango tree phyllosphere is capable of controlling anthracnose and promoting plant growth ( Balderas-Ruíz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, chemical fungicides are gradually becoming inoperative. Therefore, the use of bacterial biocontrol agents to control rice blast is gaining attention [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%